تحليل واقع الواردات السلعية السورية - الكفري مصطفى العبد الله; أغا عمار ناصر; البشير أمين بشير (Latakia University Journal - Economic and Legal Sciences Series, 2019)
تلبي الواردات السلعية حاجات الاقتصاد الأساسية من سلع استهلاكية و رأسمالية ومواد خام ضرورية للعملية الإنتاجية، إذ تعتمد مختلف القطاعات الاقتصادية على الواردات السلعية، ويلاحظ في السنوات الأخيرة تطور حجم هذه الواردات السلعية بنسب كبيرة أدت إلى تضخيم قيمة هذه الواردات في سورية . لذلك تحاول هذه الدراسة تحليل واقع وبنية الواردات السلعية السورية خلال الفترة (2000 – 2008 ) وذلك من خلال التحليل الوصفي والتحليل القياسي، ومحاولة تبيان بنية هذه الواردات السلعية وتوزيعها الجغرافي، وكذلك محاولة تبيان أثر بعض المتغيرات الاقتصادية على هذه الواردات، وقد توصلت هذه الدراسة إلى أن أغلب الواردات السلعية هي من المواد الكمالية ذات القيمة المضافة العالية التي تلحق خسارة كبيرة في الاقتصاد الوطني، وكذلك توصّلت إلى أن معظم المتغيرات المعتمدة ذات دلالة إحصائية معنوية . Commodity imports meet the needs of the economy, basic consumer goods and capital and raw materials essential to the productive process; it depends on various economic sectors, commodity imports, and as noted in recent years, we see that the evolution of the volume of imports of these commodities to a great extent led to the inflation of the value of these imports in Syria. So this study attempts to analyze the reality and the structure of commodity that Syria imports during the period (2000 - 2008) and through descriptive analysis and analysis of the standard, and an attempt to show the structure of these imports of goods and their geographical distribution, and also an attempt to demonstrate the impact of some economic variables on these imports. This study found out that most of the imports of goods are luxury items with high added value, which caused a great loss to the national economy, and also that most of the variables have abstract statistical indications.